More on Dongxiang Vowel System - Viktoria V. Kukanova; Zayana I. Chushkaeva (Oriental Studies)
Introduction. Dongxiang is a southern Mongolic language containing a variety of archaic features that seem promising for comparative historical linguistics. Goals. The study attempts an analysis of Dongxiang vowel patterns introduced in works authored by Russian and foreign scientists. Materials. The article focuses on published Dongxiang language materials dealing with phonetic features of this southern Mongolic language. Results. The vowel phonetic system of Dongxiang — reported to comprise a total of five to seven sounds — has been approached by a number of scholars, such as B. Todaeva, Ma Guoliang and Liu Zhaoxiong, Nademude, Buhe, A. Ibrahim, Ma Guozhong and Chen Yuanlong, Deligerma. However, the only researcher to have identified certain phonemes is A. Ibrahim. So, despite the academic insights, issues of phonemic statuses for some vowel sounds still remain unresolved. The available works contain no concurrent views on the Dongxiang vowel system, the latter to comprise even differing numbers of sounds in classifications authored by different researchers. Our comparative review of the different classifications reveals those tend to differentiate vowel sounds by position (front, central, and back ones) and by tenseness (close, mid, and open ones). Labiality is also indicated as a defining characteristic but vowel lengths still remain unattended by the researchers.